2020
DOI: 10.1292/jvms.20-0137
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-19 enhances cytokine production induced by lipopolysaccharide and inhibits cytokine production induced by polyI:C in BALB/c mice

Abstract: Interleukin (IL)-19 is a cytokine of the IL-10 family. There are many reports on the involvement of IL-19 in several human diseases. There also are many reports elucidating the role of IL-19 using mouse disease models. Most reports use C57BL/6 mice, whereas few reports use BALB/c mice, in terms of the mouse disease model that the researchers used in the present study. To date, research on the role of IL-19 is diversified, yet some basic mechanisms are still unclear. In this study, we administered lipopolysacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…To avoid strain-specific results and limit the potential bias in the assessment of the immune responses, we used distinct HA strains on a C57Bl/6-129 background (colony at CHOP) or BALB/c background (colony at Indiana University). The HA phenotype is similar between these strains but immune responses to pathogens, proteins, and gene therapy is known to differ (58)(59)(60)(61)(62)(63). Further, we used two distinct murine (m) BAFF mAbs: 1) clone 10F4 which is a hamster IgG1 mAb with a half-life of ~2 weeks 64) and 2clone Sandy-2 which is a mouse IgG1 mAb with a half-life of ~10 days (65).…”
Section: Inhibitor Prevention and Eradication Studies In Ha Mouse Modelsmentioning
confidence: 99%
“…To avoid strain-specific results and limit the potential bias in the assessment of the immune responses, we used distinct HA strains on a C57Bl/6-129 background (colony at CHOP) or BALB/c background (colony at Indiana University). The HA phenotype is similar between these strains but immune responses to pathogens, proteins, and gene therapy is known to differ (58)(59)(60)(61)(62)(63). Further, we used two distinct murine (m) BAFF mAbs: 1) clone 10F4 which is a hamster IgG1 mAb with a half-life of ~2 weeks 64) and 2clone Sandy-2 which is a mouse IgG1 mAb with a half-life of ~10 days (65).…”
Section: Inhibitor Prevention and Eradication Studies In Ha Mouse Modelsmentioning
confidence: 99%
“… 39 Previous research has shown that some cytokines, such as chemokine (C-C matrix) ligand 2 (CCL2), CCL3, CCL4, TNF-α, and IL-12p70, were significantly decreased in LPS-treated BALB/c IL-19 -/ - , suggesting that IL-19 may enhance the LPS response in BALB/c mice. 40 However, there are currently no results of similar experiments using C57BL/6 mice. 40 We used LPS to treat IL-19 -/- and WT C57BL/6 mice in this experiment, which led to increased BV/TV and Tb.N, and decreased Tb.Sp.…”
Section: Discussionmentioning
confidence: 99%
“… 40 However, there are currently no results of similar experiments using C57BL/6 mice. 40 We used LPS to treat IL-19 -/- and WT C57BL/6 mice in this experiment, which led to increased BV/TV and Tb.N, and decreased Tb.Sp. 36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation